Handbook of the economics of education. - Hanushek, Eric A. (Elsevier, 2023)
The Handbook of the Economics of Education describes the research frontier in key topical areas and sets the agenda for further work. Modern analysis in the economics of education has made tremendous strides in understanding fundamental issues related to the production of human capital and the impact of varying institutional features of education systems. By bringing together some of the world's leading scholars, this volume provides a unique view of scholarship in the area. The international perspectives of the editors - Hanushek at Stanford, Machin at LSE, and Woessmann at Munich - leads to a volume with something for all researchers. Topics range from the economics of early childhood education to inequality in society to cash transfers in developing countries. Identification and evaluation of the state of the art. Clear descriptions of the meaning of existing research and the most likely avenues for the future Insights into how policy interventions in education can help or hurt human capital outcomes--